Management of gastric conduit retention following hybrid and minimally invasive esophagectomy for esophageal cancer: Two retrospective case series. (2017) - Farnes, Ingvild; Johnson, Egil; Johannessen, Hans-Olaf
Highlights: About 5% of patients experience long-term gastric conduit retention. Two patients with hybrid and total minimally invasive Ivor-Lewis esophagectomy experienced long-term retention of the conduit. Initial too wide hiatal opening or a combination of a redundant conduit and a too narrow hiatus led to conduit retention. Reoperation involved open thoracoabdominal access for mobilization, reduction and diaphragmatic fixation of the herniated conduit. One patient had an excellent result whilst the other improved despite a limited degree of reherniation of the conduit. Abstract: Introduction: Following esophagectomy about 5% of patients experience long-term gastric conduit retention. We report two patients with surgical correction for this problematic condition. This case series is a retrospective, non-consecutive single center report. Presentation of cases: A slender female aged 76 (patient 1) and an obese man aged 69 (patient 2) with esophageal cancer, underwent hybrid and total minimally invasive Ivor-Lewis esophagectomy, respectively. The conduit was tubularized, and the stapled anastomosis located above carina. The crura were divided in patient 1. Contrast enema revealed a straight (patient 1) or redundant (patient 2) thoracic conduit. Conduit retention in patient 1 began after 47 months. After 61 months reoperation was performed with open thoracoabdominal access for mobilization, abdominal reduction and diaphragmatic suture fixation of the herniated conduit. Symptoms improved and oral nutrition is still sufficient after 8 months. Patient 2 had clinically significant retention after 15 months, despite using pyloric Botox injection and expandable metal stenting. At laparoscopic reoperation after 27 months a partial conduit mobilization and refixation were unsuccessful, but an accidental colonic hiatal hernia was taken down. After 28 months a second reoperation was performed, similar to patient 1. Fifteen months afterwards the patient still ate sufficiently, but a limited double reherniation had occurred. Discussion: Long-term retention post-esophagectomy often start with an initial redundant conduit, that can increase from food-induced stretching and declive emptying against gravity. A wide hiatal opening probably also predispose to conduital herniation. Conclusions: Conduit retention improved after mobilization, reduction and its hiatal fixation. A too wide or narrow hiatal opening must be avoided to prevent herniation.